2017
DOI: 10.1002/ajoc.201700216
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functionalized 4‐Fluoropyridazines

Abstract: Ar oute to 4-fluoropyridazines by a[ 2 + +1]/[3+ +2] cycloaddition sequence betweena na cetylenic derivative, ad ifluorocarbenes ource,a nd ad iazo compound is reported. This approach is highly modulara nd compatiblew ith ab road range of functional groups. The protocol does not require the isolation of any reactive intermediates and,t hus, allows for access to aw ide range of 4-fluoropyridazines in as ingle synthetics tep from simple alkynes. Furthermore, these fluorinated compounds can be easily diversified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…In 2017, Cossy and coworkers reported a [3 + 2]‐cycloaddition of CF 3 CHN 2 with difluorocyclopropenes 100 to access functionalized 4‐fluoropyridazines 101 (Scheme 47) [64]. This base‐catalyzed protocol was compatible with several difluorocyclopropenes 100 to deliver the targeted products in good to excellent yields efficiently.…”
Section: Application Of Trifluorodiazoethane In Cf3‐heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Cossy and coworkers reported a [3 + 2]‐cycloaddition of CF 3 CHN 2 with difluorocyclopropenes 100 to access functionalized 4‐fluoropyridazines 101 (Scheme 47) [64]. This base‐catalyzed protocol was compatible with several difluorocyclopropenes 100 to deliver the targeted products in good to excellent yields efficiently.…”
Section: Application Of Trifluorodiazoethane In Cf3‐heterocyclesmentioning
confidence: 99%
“…Multicomponent synthesis of trifluoromethylated isoquinolinonesusing o-(trimethylsilyl)phenyl triflate 97 as an aryne precursor in the presence of CsF and TEBAC ([Et 3 NBn] + Cl À ) in high yields under mild reaction conditions.4.13 | Synthesis of CF 3 -substituted pyridazinesIn 2017, Cossy and coworkers reported a [3 + 2]cycloaddition of CF 3 CHN 2 with difluorocyclopropenes 100 to access functionalized 4-fluoropyridazines 101 (Scheme 47)[64]. This base-catalyzed protocol was compatible with several difluorocyclopropenes 100 to deliver the targeted products in good to excellent yields efficiently.Mechanistically, [3 + 2]cycloaddition of 1 with difluorocyclopropenes gives the pyrazoline I.…”
mentioning
confidence: 99%
“…Recently, our group reported the synthesis of α-(trifluoromethyl)pyridazines 68 by using a [2+1]/[3+2]-cycloaddition sequence between a terminal alkyne, a difluorocarbene and (trifluoromethyl)diazomethane. [17] More specifically, in the presence of a difluorocarbene, alkynes 64 underwent a [2+1]-cycloaddition to form 3,3-difluorocyclopropenes 65. These cyclopropenes reacted in a [3+2]-cycloaddition with (trifluoromethyl)diazomethane to afford cyclopropanopyrazolines 66.…”
Section: [2+1]/[3+2]-cycloaddition Sequencementioning
confidence: 99%
“…In addition, due to the presence of a fluorine atom at the C4 position of the pyridazine ring, pyridazines 68 could be further functionalized by applying a nucleophilic aromatic substitution (S N Ar), giving access to a wide diversity of (trifluoromethyl)pyridazines 69 (Scheme 23). [17] Scheme 23. Functionalization of α-(trifluoromethyl)pyridazines 68 using a S N Ar to access α-(trifluoromethyl)pyridazines 69.…”
Section: [2+1]/[3+2]-cycloaddition Sequencementioning
confidence: 99%
“…4 In 2017, Cossy and coworkers found that the reaction of CF 3 CHN 2 with strained alkenes such as difluorocyclopropenes proceeds in a [3 + 2] cycloaddition/cyclopropane ring-opening process, thus providing a novel entry to 6-CF 3 -pyridazines (Scheme 1b). 5 Recently, our group disclosed a silver-catalyzed [3 + 3] cycloaddition of glycine imines with CF 3 CHN 2 for the synthesis of CF 3 -(tetrahydro)triazines (Scheme 1c). 6 On this basis, we envisioned that 2H-azirines, as highly versatile and strained imines, may undergo a [3 + 3] annulation reaction with CF 3 CHN 2 to furnish the dihydrotriazines, which would be sequentially oxidized to afford CF 3 -triazines (Scheme 1d, top).…”
mentioning
confidence: 99%